The development of the teacher's virtues in the face of school violence (Research, Society and Development, 2019)
This study aims to reflect on the development of the virtues of the teacher, described by Ecco (2015) in a Freirean perspective. This is a reflexive study based on the conceptions of the above-mentioned authors, in agreement with problematizations about two reports compiled from the field diary of a teacher, collected from two students of a public school. In between the lines, it is understood that Ecco's study of the Freirean legacy does not impose fixed methodologies, but rather provides an even broader set of reflections on the virtues of the teacher and his role in the classroom. Through the reports described, it was noticed that the teaching virtues are increasingly present in the daily life of schools, given the significant social role that the teacher plays in this context. In this sense, it is considered relevant the teacher reflection on their own virtues, so that a healthy development and sensitive to the demands of their students occurs.